2019
DOI: 10.1002/gepi.22199
|View full text |Cite
|
Sign up to set email alerts
|

Subset testing and analysis of multiple phenotypes

Abstract: Meta‐analysis of multiple genome‐wide association studies (GWAS) is effective for detecting single‐ or multimarker associations with complex traits. We develop a flexible procedure (subset testing and analysis of multiple phenotypes [STAMP]) based on mixture models to perform a region‐based meta‐analysis of different phenotypes using data from different GWAS and identify subsets of associated phenotypes. Our model framework helps distinguish true associations from between‐study heterogeneity. As a measure of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…We therefore used CPBAYES and STAMP, which borrow strength across groups of cancers and/or medical conditions, as complementary methods to discern significant associations that would otherwise have been missed. 21,22 In particular, the global tests of association provided by STAMP indicated that grouped immunosuppressive, autoimmune, and allergic conditions were broadly associated with outcomes for specific cancers. These results suggest that immunocontainment has multifaceted aspects affecting the control of cancers originating from different organ systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore used CPBAYES and STAMP, which borrow strength across groups of cancers and/or medical conditions, as complementary methods to discern significant associations that would otherwise have been missed. 21,22 In particular, the global tests of association provided by STAMP indicated that grouped immunosuppressive, autoimmune, and allergic conditions were broadly associated with outcomes for specific cancers. These results suggest that immunocontainment has multifaceted aspects affecting the control of cancers originating from different organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, visual inspection of the volcano plots in Figure 1 reveals clear patterns for associations with P ‐values between these two thresholds. We therefore used CPBAYES and STAMP, which borrow strength across groups of cancers and/or medical conditions, as complementary methods to discern significant associations that would otherwise have been missed 21,22 . In particular, the global tests of association provided by STAMP indicated that grouped immunosuppressive, autoimmune, and allergic conditions were broadly associated with outcomes for specific cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation